2021
DOI: 10.1126/scitranslmed.abe6805
|View full text |Cite
|
Sign up to set email alerts
|

Temporal multi-omics identifies LRG1 as a vascular niche instructor of metastasis

Abstract: A systems-biology endothelial cell screen has established the vascular systems map of early metastatic colonization and identified the TGFb pathway specifier as therapeutic target of metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 69 publications
(114 reference statements)
1
41
0
Order By: Relevance
“…In addition, LRG1 has been identified as a useful biomarker to distinguish between patients with active or inactive systemic juvenile idiopathic arthritis and in patients with rheumatoid arthritis during Tocilizumab treatment 8 , 59 . Taking these reports into account, together with other studies where the IL-6/STAT3 axis has been implicated in the regulation of LRG1 20 , 60 – 62 and a study showing that IL-6 promotes defective angiogenesis 34 , we explored the potential transcriptional regulation of LRG1 by IL-6. We showed that IL-6 activated LRG1 transcription to promote angiogenesis with reduced mural cell coverage through the phosphorylation and binding of STAT3 to its conserved consensus site on the LRG1 gene promoter.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, LRG1 has been identified as a useful biomarker to distinguish between patients with active or inactive systemic juvenile idiopathic arthritis and in patients with rheumatoid arthritis during Tocilizumab treatment 8 , 59 . Taking these reports into account, together with other studies where the IL-6/STAT3 axis has been implicated in the regulation of LRG1 20 , 60 – 62 and a study showing that IL-6 promotes defective angiogenesis 34 , we explored the potential transcriptional regulation of LRG1 by IL-6. We showed that IL-6 activated LRG1 transcription to promote angiogenesis with reduced mural cell coverage through the phosphorylation and binding of STAT3 to its conserved consensus site on the LRG1 gene promoter.…”
Section: Discussionmentioning
confidence: 98%
“…This is currently most evident in the eye and kidney, where it plays a central role in the vascular dysfunction observed in models of retinal neovascularisation and diabetic kidney disease and is consistent with raised LRG1 levels in patients with these diseases 15 17 . Moreover, in cancer, where there is an emerging body of evidence for a pathogenic role for LRG1 14 , 18 , the induction of LRG1 in tumour endothelial cells has also been shown to contribute to pathological neovascularisation 19 and priming the vascular metastatic niche 20 establishing this secreted glycoprotein as a new vasculopathic molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In conditions of altered homeostasis that typically accompany disease, transcription of the Lrg1 gene has been reported to be highly upregulated in endothelial cells [ 4 , 70 , 73 75 ], several types of epithelial cells [ 15 , 17 , 26 , 28 , 68 , 76 ], fibroblasts [ 34 , 57 , 70 , 77 ] and myeloid cells [ 11 , 56 , 72 , 78 – 81 ] including microglia [ 82 ] (Fig. 5 ).…”
Section: Reviewmentioning
confidence: 99%
“…3 F). As a result, it plays a key role in conditioning the vascular bed for metastatic colonization, possibly by increasing the number of pro-metastatic perivascular cells [ 75 ]. This study also revealed that the contribution of LRG1 secreted by the vascular compartment is far more important than that synthesised by the liver, and that targeting LRG1 therapeutically may have utility in restricting metastatic cancer.…”
Section: Reviewmentioning
confidence: 99%
“…Some of these changes may affect blood vessels, as recently shown for leucine-rich alpha-2-glycoprotein 1 (ref. 54 ). However, our findings indicate that the four vascular niche genes are not induced by secreted factors from primary tumors.…”
Section: Discussionmentioning
confidence: 99%